2015
DOI: 10.3138/jvme.1114-115r
|View full text |Cite
|
Sign up to set email alerts
|

Development, Evaluation, and Evolution of a Peer Support Program in Veterinary Medical Education

Abstract: The majority of peer support programs in UK universities focus on academic support (e.g., through peer-assisted learning programs). Following student consultation, a pilot pastoral-based student peer support program was developed and implemented in a UK veterinary school. Thirty-one students were trained in the pilot year, and continued with the program to the end of the academic year (and beyond). The trainees were asked for feedback at the end of training and at the end of the year; the rest of the student b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Peer support training also had positive impacts on general communication skills (Spielman et al, 2015;Steinbauer, 1998) and speci c empathetic and re ection skills (Aladag & Tezer, 2009;Brenton, 2000;Martin, 1998). Peer supporters had also reported self-development (Spielman et al, 2015), increased con dence in supporting peers (Eisenstein et al, 2019;Hart et al, 2018), decreased nervousness and increased self-awareness (Abu-Rasain & Williams, 1999). A longitudinal study on secondary school peer supporters' pre-and post-peer program participation found signi cant improvement in peer support skills and understanding (Eisenstein et al, 2019), which corroborates the results from our study.…”
Section: Criterion Validitymentioning
confidence: 99%
See 3 more Smart Citations
“…Peer support training also had positive impacts on general communication skills (Spielman et al, 2015;Steinbauer, 1998) and speci c empathetic and re ection skills (Aladag & Tezer, 2009;Brenton, 2000;Martin, 1998). Peer supporters had also reported self-development (Spielman et al, 2015), increased con dence in supporting peers (Eisenstein et al, 2019;Hart et al, 2018), decreased nervousness and increased self-awareness (Abu-Rasain & Williams, 1999). A longitudinal study on secondary school peer supporters' pre-and post-peer program participation found signi cant improvement in peer support skills and understanding (Eisenstein et al, 2019), which corroborates the results from our study.…”
Section: Criterion Validitymentioning
confidence: 99%
“…In the peer support literature, studies found that training programs increased peer supporters' recognition of suicide symptoms (Hennig et al, 1998) and decreased their stigmatizing beliefs (Hart et al, 2018). Peer support training also had positive impacts on general communication skills (Spielman et al, 2015;Steinbauer, 1998) and speci c empathetic and re ection skills (Aladag & Tezer, 2009;Brenton, 2000;Martin, 1998). Peer supporters had also reported self-development (Spielman et al, 2015), increased con dence in supporting peers (Eisenstein et al, 2019;Hart et al, 2018), decreased nervousness and increased self-awareness (Abu-Rasain & Williams, 1999).…”
Section: Criterion Validitymentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the extensive literature on peer support programs for individuals with serious mental illness, few studies have investigated peer support programs for mental health promotion in colleges and vocational schools. Most studies on school-based mental health peer support were conducted in secondary or high schools [1,13,15,20,21,38,41] and one was conducted in a veterinary school [40]. Out of the four studies found that were conducted among college students, two had small sample sizes of 20 to 30 peer supporters [2,4], one collected only qualitative data [4], and two did not collect any primary data [22,42].…”
mentioning
confidence: 99%